2019
DOI: 10.3390/agronomy10010024
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation in Fatty Acid Composition of Diverse World Soybean Germplasms Grown in China

Abstract: Soybean (Glycine max L. Merr.) is one of the most important crops in the world. Its major content of vegetable oil made it widely used for human consumption and several food industries. To investigate the variation in seed fatty acid composition of soybeans from different origins, a set of 633 soybean accessions originated from four diverse germplasm collections—including China, United States of America (USA), Japan, and Russia—were grown in three locations, Beijing, Anhui, and Hainan for two years. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 63 publications
(100 reference statements)
7
27
0
Order By: Relevance
“…The corresponding loading plot revealed oleic acid and palmitic acid as the most discriminative variables along PC1 and PC2, respectively ( Fig 4D, Table 2). These observations signify that oleic acid and palmitic acid could selectively be targeted to categorize a large population of soybeans [32]. The relationship between the variables resulted from Pearson correlation analysis was also consistent with their grouping observed in the cluster analysis (Table 3).…”
Section: Cluster Principal Component and Correlation Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…The corresponding loading plot revealed oleic acid and palmitic acid as the most discriminative variables along PC1 and PC2, respectively ( Fig 4D, Table 2). These observations signify that oleic acid and palmitic acid could selectively be targeted to categorize a large population of soybeans [32]. The relationship between the variables resulted from Pearson correlation analysis was also consistent with their grouping observed in the cluster analysis (Table 3).…”
Section: Cluster Principal Component and Correlation Analysissupporting
confidence: 80%
“…Among all the soybeans, soybeans BL19 and BL17 had the highest, whereas soybeans YG47 and PY33 had the lowest palmitic and stearic acid contents, respectively. Soybean PY31 had the highest oleic acid and the lowest linoleic acid contents, whereas soybean BL16 had the lowest oleic acid and the highest linoleic acid contents at the same time indicating the trade-off relationship between these two fatty acids [8, 29, 32]. Soybean PY31 also displayed the lowest level of linolenic acid while soybean BL19 had the highest level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These ranges were comparable with those reported by Kim et al [ 9 ] but slightly wider than those reported by Shin et al [ 34 ]. In other studies, a less wide range of oleic acid and more wide range of linoleic acid and linolenic acid were reported [ 29 , 36 ]. In addition to differences in the genotype, discrepancies in the number of studied soybean genetic resources could cause such variations.…”
Section: Resultsmentioning
confidence: 99%
“…Direct use of edible oils in cell permeability studies was not successful due to the poor viability of the cell monolayers upon treatment with oils. Linoleic acid (~54%) (Abdelghany et al., 2020) and lauric acid (~50%) (Seneviratne & Dissanayake, 2005) are the major fatty acids in soybean oil and coconut oil, respectively. Linoleic acid represents a long chain polyunsaturated fatty acid, and lauric acid represents a medium chain saturated fatty acid.…”
Section: Discussionmentioning
confidence: 99%